Exposure to respirable dust and factors associated with abnormal pulmonary function among stone diggers in Kayole quarries, Nairobi City County, Kenya - Mwangi, Fredah Wanjiku; Warutere, Peterson; Nyambura, Anthony W. (International Journal Of Community Medicine And Public Health, 2023)
Background: In Kenya, the quarry industry suffers several constraints: some quarry workers get injured, others get chronic diseases, while some die. This study assessed occupational exposure to respirable dust and factors associated with abnormal pulmonary function among quarry stone diggers in Mihang’o and Matopeni quarries in Kayole Nairobi City County, Kenya. Methods: The study was done in Mihang’o and Matopeni quarries. An analytical cross-sectional design was used and a sample size of 165 respondents was taken. An interviewer administered semi structured questionnaire. Spirometry tests were done by a qualified technician to assess pulmonary function. Respirable dust levels were determined with the aid of a particle counter. Descriptive statistics like frequency, means were used to summarize data and results were presented in frequency tables and graphs. Chi square tests and logistic regression were done. T tests were done to compare the means of dust levels in the two quarries. Results: This study found the daily mean levels of PM2.5 and PM10 were higher than the levels recommended by WHO. The age of the respondents, presence of respiratory symptoms, years of work experience, nostril covering, and smoking were factors associated with abnormal pulmonary function at (p≤0.05). Conclusions: In conclusion, chronic exposure to quarry dust increases the risk of developing respiratory symptoms and abnormal pulmonary function. This study recommended that routine particulate matter monitoring should be done in Nairobi quarries to provide data that can inform decisions on air pollution control actions.